Recent advances in TAM mechanisms in lung diseases - Jiaqi Ban; Jiayi Qian; Chi Zhang; Jun Li (Journal of Translational Medicine)
Abstract TYRO3, MERTK, and AXL receptor tyrosine kinases, collectively known as TAM receptors, play a vital role in maintaining lung tissue homeostasis by regulating integrity and self-renewal. These receptors activate signalling pathways that inhibit apoptosis, promote cell proliferation and differentiation, mediate cell adhesion and migration, and perform other essential biological functions. Additionally, TAM receptors are implicated in mechanisms that suppress anti-tumor immunity and confer resistance to immune checkpoint inhibitors. Disruption of the homeostatic balances can lead to pathological conditions such as lung inflammation, fibrosis, or tumors. Recent studies highlight their significant role in COVID-19-induced lung injury. However, the exact mechanisms by which TAM receptors contribute to lung diseases remain unclear. This article reviews the potential mechanisms of TAM receptor involvement in disease progression, focusing on lung inflammation, fibrosis, cancer, and COVID-19-induced lung injury. It also explores future research aspects and the therapeutic potentials of targeting TAM receptors, providing a theoretical foundation for understanding lung disease mechanisms and identifying treatment targets.